Acceptance and commitment therapy combined with usual care improves psychosocial outcomes and reduces complications in patients with permanent colostomies after colorectal cancer surgery: a retrospective cohort study - Shi, Yali; Yu, Hongwei; Wang, Lihui; Zhang, Haiqiang (Frontiers in Surgery, 2025)
BackgroundPermanent colostomies after colorectal cancer surgery can seriously affect patients' quality of life (QoL) and psychosocial adjustment. Research on the benefits of Acceptance and Commitment Therapy (ACT) for this group is still limited.ObjectiveTo examine whether adding ACT to standard stoma care improves self-efficacy, resilience, QoL, and stoma-related complication rates compared with standard care alone.MethodsThis single-center retrospective cohort study (2022–2024) included 120 patients with permanent colostomies. After 1:1 propensity score matching (60 patients per group, caliper = 0.2 SD), one group received an 8-session ACT program over 6 weeks alongside usual care, while the control group received usual care only. Outcomes were measured at 3 months (T1) and 6 months (T2) post-surgery. Primary outcomes were self-efficacy (C-SSES), resilience (CD-RISC), and stoma-related QoL (Stoma-QOL). Secondary outcomes included stoma complications. Linear mixed-effects models and conditional logistic regression were applied for analysis.ResultsSignificant improvements over time were observed in the ACT group compared with controls (all p < 0.001). At T2, the ACT group showed higher self-efficacy [mean difference (MD) = 14.7, 95% CI: 10.9–18.5; d = 0.92], resilience (MD = 11.1, 95% CI: 7.8–14.4; d = 0.89), and QoL (MD = 12.3, 95% CI: 8.7–15.9; d = 0.86). ACT also reduced overall complication rates (33.3% vs. 51.7%; OR = 0.48, 95% CI: 0.24–0.96), particularly dermatitis (16.7% vs. 31.7%; OR = 0.43, 95% CI: 0.19–0.99). At T2, self-efficacy, resilience, and QoL were strongly correlated (all r ≥ 0.65, p < 0.001).ConclusionAdding ACT to routine stoma care improves self-efficacy, resilience, and quality of life, while also lowering complication rates in patients with permanent colostomies. These findings suggest ACT is a valuable supportive therapy in stoma care.